الثقة بالنفس لدى طالبات الجامعة ذوات اضطرابات النطق والكلام - عبدالهادي، سهير محمد محمد توفيق (مؤسسة التربية الخاصة والتأهيل التربوي, 2020)
The aim of the study was to find the self-confidence of some university students with speech and language disorders. This includes examining the factors behind their low level of self-confidence which lead to finding possible solutions to the psychological phenomena associated with low level of spoken language and self-confidence due to speech and language disorders. The effectiveness of this group on social communication and achievement and contribute to provide psychological support for efforts to treat and qualify this category, will use the study will use descriptive method, and the final sample of the study consists of (20) students aged 19-22 years (10) students suffering from disorders of speech and language based on their medical diagnosis, (10) of the normal students will be applied to them all Stanford - Intermediate (the Fifth picture), and the quality of speech and language (researcher preparation), and test the growth of jobs The results have proven the development of spoken language and self-confidence among university students who are troubled by speech and language through several factors (linguistic communication, social communication, self-confidence, ability to solve problems, Feeling of psychological satisfaction), and there are significant differences counted Vision among students with impairments and regular students in the direction of regular students, and predictable level of self-confidence in the students speech and language impairments through the degree of disorder pronunciation.
هدفت الدراسة لمعرفة الثقة بالنفس لدى بعض الطالبات الجامعيات ذوات اضطرابات النطق والكلام، ويتضمن ذلك فحص العوامل الكامنة وراء تدنى مستوى الثقة بالنفس لديهم والتي تؤدى إلي إيجاد حلول ممكنة لمعالجة الظواهر النفسية المرتبطة بانخفاض كل من مستوى اللغة المنطوقة والثقة بالنفس نتيجة لوجود اضطرابات في النطق والكلام مما يزيد من فعالية هذه الفئة علي التواصل اجتماعيا وتحصيلياً ويسهم بتقديم الدعم النفسي للجهود الرامية إلى علاج وتأهيل هذه الفئة، وسوف يستخدم في الدراسة المنهج الوصفي، وتتكون العينة النهائية للدراسة من ‎(20) طالبة تتراوح أعمارهن من (19-22) عاماً موزعات وفق ما يلي (10) طالبات يعانون من اضطرابات في النطق والكلام بناء على تشخيصهم طبياً، (10) من الطالبات العاديات طبق عليهم جميعاً مقياس ستانفورد - بينية (الصورة الخامسة)، ومقياس جودة النطق والكلام (إعداد الباحثة)، واختبار نمو وظائف اللغة إعداد الرفاعي ‎(2009)، ومقياس الثقة بالنفس )إعداد الباحثة)، وأسفرت عن تتمية اللغة المنطوقة والثقة بالنفس لدى طالبات الجامعة المضطربات في النطق والكلام من خلال عدة عوامل تتمثل في (التواصل اللغوي، التواصل الاجتماعي، الثقة بالنفس، القدرة على حل المشكلات، الشعور بالرضا النفسي)، ووجود فروق ذات دلالة إحصائية بين الطالبات المضطربات والعاديات في اتجاه العاديات، ويمكن التتبؤ بمستوى الثقة بالنفس لدى مضطربات النطق والكلام من خلال درجة اضطراب النطق.
Keywords: طلبة الجامعة -- الثقة بالنفس -- اضطرابات النطق والكلام -- كلية الدراسات الإنسانية -- جامعة الأزهر